(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This research is motivated by the Islamic legal perspective on the political rights of disabled individuals post-presidential and legislative elections in the Tanah Datar Regency. It focuses on the Islamic legal viewpoint regarding the political rights of disabled individuals as outlined in Article 13 of Law Number 8 of 2016 concerning Persons with Disabilities in the Tanah Datar region and the support provided by the General Election Commission (KPU) during the elections. In practice, there are still disabled individuals who do not exercise their voting rights due to limited accessibility. This is an empirical research study, which examines how the law operates in society. The primary data sources used are Law Number 8 of 2016 and interviews conducted with the KPU, Bawaslu,disabled individuals. The research findings reveal that the Islamic legal perspective on the political rights of disabled individuals post-legislative and presidential elections in the Tanah Datar Regency is that Islam does not differentiate between individuals based on physical limitations, wealth, but rather emphasizes the importance of faith and piety. Similarly, in Indonesia, the state has accommodated the rights of disabled individuals in terms of both public accessibility and their political rights. This is governed by Law Number 8 of 2016 concerning persons with disabilities and is also accommodated in the Election Law, Law Number 7 of 2017. However, in practice, full accessibility for disabled individuals to exercise their voting rights is not yet entirely met due to the lack of facilities that support disabled individuals in casting their votes